Training Patient Stakeholders Builds Community Capacity, Enhances Patient Engagement in Research - Hannah Cole McGrew; Lidia Regino; Molly Bleecker; Maria Tellez; Blanca Pedigo; Denisse Guerrero; Virginia Sandoval; Loida Varela; Janet Page-Reeves (The University of Alabama, 2022)
Our philosophical framework for research with low-income Latino patients with diabetes prioritizes hiring research staff who share the culture and language of the population of study. Inclusive research design requires an active role by patient stakeholders with training opportunities in a collaborative learning environment to allow patient stakeholder data collectors (PSDCs) to build on existing strengths and expertise. To develop this manuscript, our team reflected on our collective experiences in implementing research-specific trainings for PSDCs. Although our population of study is known to be difficult to recruit and retain, our PSDCs have successfully enrolled participants on schedule, and attrition is low. Although language, institutional requirements, and funding restrictions presented training challenges, we overcame these by using a flexible approach and by incorporating the data collectors' expertise in refining our protocols. We propose that our success in recruiting and retaining participants is a reflection of our engaged research strategy and framework and demonstrates that engagement promotes better science. However, our experience also demonstrates research institutions need to make policy and infrastructural improvements to reduce barriers and make engaged approaches more feasible.